The Introduction for Number Symbols in Children Aged 4-5 Years through Mathematics Play Activities - Syafdaningsih, Syafdaningsih; Utami, Febriyanti (Indonesian Journal of Early Childhood Education Studies, 2021)
The introduction of number symbols in early childhood is the basis of learning mathematics. One form of educational services provided to early childhood is adjusted to the principle of learning while playing. Playing is one method that can be used in introducing the concept of symbol numbers. This study aims to provide an overview of the introduction of number symbols in children aged 4-5 years through playing mathematics. The method used in this research is a qualitative descriptive research method with literature study or literature study. This research is focused on the introduction of number symbols in children 4-5 years based on the stages of number symbol recognition. In addition, it also provides an overview of the introduction of the symbol of numbers by playing math activities that can be done at school or at home. The recognition of number symbols is an important part of learning mathematics because the introduction of number symbols at an early age will have an effect on future children's mathematics achievement. Mathematics playing activities are effectively used in the introduction of number symbols both at school and at home. Playing mathematics activities provides benefits for early childhood in learning mathematics, especially the introduction of number symbols. This is evident from the results of previous studies and other literature relating to the introduction of number symbols in early childhood through playing mathematics.